Peran Mindfulness dalam Meningkatkan Motivasi Belajar pada Mahasiswa Gen-Z - Rohman; Desty Endrawati Subroto; Khairunnisa Azra Amalina; Ovi Nabila; M. Ahyudin; Dewi Yanah (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2025)
Learning motivation is the drive that encourages individuals to remain enthusiastic about learning. Previous research has explained various forms of motivation, such as internal and external motivation. One aspect of internal motivation is self-awareness or Mindfulness. However, research on Mindfulness as a factor influencing learning motivation, particularly in Generation Z, is still quite limited. Therefore, this study aims to examine the role of Mindfulness in enhancing learning motivation in Generation Z. This research uses purposive sampling to select samples that meet the research criteria. The participants involved are Generation Z individuals aged between 12 and 27 years, residing in Banten, and currently enrolled as active students. To measure the level of learning motivation, the Academic Motivation Scale (AMS) is used, while the Five Facet Mindfulness Scale (FMMQ-10) is used to measure the level of Mindfulness. The results of the study show a significant positive relationship between Mindfulness and learning motivation, with a regression coefficient of 0.152. This means that the higher an individual's level of Mindfulness, the higher their learning motivation will be. These findings suggest that Mindfulness can play an important role in improving learning motivation, especially when applied alongside other supporting factors such as social support, emotional regulation, and a conducive learning environment. This study provides evidence that a Mindfulness-based approach has the potential to be applied in strategies to enhance learning motivation. Therefore, the development of programs integrating Mindfulness practices into students' daily lives, particularly among Generation Z, could be an effective step in improving the quality of their learning experience.